2013
DOI: 10.1038/nature12359
|View full text |Cite
|
Sign up to set email alerts
|

The molecular logic for planarian regeneration along the anterior–posterior axis

Abstract: The planarian Dugesia japonica can regenerate a complete individual from a head, trunk or tail fragment via activation of somatic pluripotent stem cells. About a century ago, Thomas Hunt Morgan attempted to explain the extraordinary regenerative ability of planarians by positing two opposing morphogenetic gradients of formative "head stuff" and "tail stuff" along the anterior-posterior axis. However, Morgan's hypothesis remains open to debate. Here we show that extracellular signal-related kinase (ERK) and Wnt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
160
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 24 publications
4
160
1
Order By: Relevance
“…However, our findings indicate that β-CATENIN-1 could be a component of both the anterior and the posterior organizers, and that it is the fine-tuning of β-CATENIN-1 that is essential for the organizing function in each pole. This is further supported by the observation that β-catenin-1 inhibition restores the ability to regenerate a head in anterior wounds in planarian species that cannot regenerate anteriorly (Liu et al, 2013;Sikes and Newmark, 2013;Umesono et al, 2013). Similarly, β-CATENIN-1 stabilization also restores the ability to regenerate anterior wounds in these animals, even though this experiment causes the expected polarity reversal and the planarians develop a two-tailed phenotype (Liu et al, 2013;Sikes and Newmark, 2013;Umesono et al, 2013).…”
Section: A Gradient Of β-Catenin-1 Along the Ap Axismentioning
confidence: 59%
See 1 more Smart Citation
“…However, our findings indicate that β-CATENIN-1 could be a component of both the anterior and the posterior organizers, and that it is the fine-tuning of β-CATENIN-1 that is essential for the organizing function in each pole. This is further supported by the observation that β-catenin-1 inhibition restores the ability to regenerate a head in anterior wounds in planarian species that cannot regenerate anteriorly (Liu et al, 2013;Sikes and Newmark, 2013;Umesono et al, 2013). Similarly, β-CATENIN-1 stabilization also restores the ability to regenerate anterior wounds in these animals, even though this experiment causes the expected polarity reversal and the planarians develop a two-tailed phenotype (Liu et al, 2013;Sikes and Newmark, 2013;Umesono et al, 2013).…”
Section: A Gradient Of β-Catenin-1 Along the Ap Axismentioning
confidence: 59%
“…This is further supported by the observation that β-catenin-1 inhibition restores the ability to regenerate a head in anterior wounds in planarian species that cannot regenerate anteriorly (Liu et al, 2013;Sikes and Newmark, 2013;Umesono et al, 2013). Similarly, β-CATENIN-1 stabilization also restores the ability to regenerate anterior wounds in these animals, even though this experiment causes the expected polarity reversal and the planarians develop a two-tailed phenotype (Liu et al, 2013;Sikes and Newmark, 2013;Umesono et al, 2013). Nevertheless, further work will be necessary to determine which specific upstream regulators generate this context-specific behavior and enable the differential roles of nuclear β-CATENIN-1 in anterior and posterior blastemas.…”
Section: A Gradient Of β-Catenin-1 Along the Ap Axismentioning
confidence: 65%
“…However, the wealthiest accumulation of stem cells does not ensure that regeneration will take place. This concept is beautifully demonstrated by three separate studies of planarians with decreased regenerative capabilities (Sikes and Newmark, 2013;Umesono et al, 2013;Liu et al, 2013). These studies showed that the evolutionary loss of head regeneration observed in posterior fragments of some planarian species was not due to insufficient populations of stem cells, but by differences in expression levels of components in the conserved wnt/b-catenin developmental pathway.…”
Section: Labib Rouhana and Junichi Tasakimentioning
confidence: 80%
“…A classic experiment by T. H. Morgan illustrated the remarkable whole-body regeneration capabilities in a planarian species: a tiny fragment just 1/279th of the original worm was able to regenerate an entire individual (Morgan, 1898). However, at least one dugesid (a species of Phagocata) is shown to fail to regenerate a new complete head following post-pharyngeal amputation (Umesono et al, 2013), suggesting a possible loss of head regeneration within this group (and possibly even within this genus, since other Phagocata species are known to regenerate a head). Among the triclads, several genera within the family Dendrocoelidae have been evaluated for regenerative ability and none are able to regenerate a complete head after amputation posterior to the pharynx (i.e., cutting within the posterior two-thirds of the primary body axis) (Lillie, 1901;Morgan, 1904;Brøndsted, 1969;Sikes and Newmark, 2013).…”
Section: * Indicates the Family Is Polyphyletic And † Indicates Thementioning
confidence: 99%